Implementasi EOQ (Economic Order Quantity) Untuk Perencanaan Dan Persediaan Pipa HDPE di PDAM Tirta Mayang Kota Jambi - Agus Topo Subekti (Jurnal INOVATOR, 2021)
The problem in this research is how to forecast HDPE pipe supply orders at PDAM Tirta Mayang Jambi using the Economic Order Quantity (EOQ) method ?. The purpose of this study was to determine the Forecasting of HDPE Pipe Supply Orders at PDAM Tirta Mayang Jambi using the Economic Order Quantity (EOQ) method. The research method used in this research is descriptive method. According to Nazir (2011), "The descriptive research method is a method of examining the status of a group of people, an object, a condition, a system of thinking, or a class of events in the present". The research objective is used to describe or explain accurately, systematically the facts in the phenomenon under study. Through this descriptive research, the researcher aims to obtain and describe how to apply the Economic Order Quantity (EOQ) inventory method in addition to the inventory method applied by PDAM Tirta Mayang Jambi City. From the analysis carried out on the HDPE pipe supply control at PDAM Tirta Mayang, Jambi City, it can be seen: (1) To forecast the need for HDPE pipe for new connections using the linear regression method. So that the total estimated number of HDPE pipes needed during 2020 is 23766 meters of pipe for one year needs. (2) The EOQ method is used to determine the number of economic orders that a company must place at 3256 meters / Order. (3) For the total cost that must be incurred by the company using EOQ is Rp. 45,448,450, while using the conventional method the company has to pay a higher cost of Rp. 88,768,650. so that it can be seen that there is a very large difference between using the EOQ method and the conventional amounting to Rp. 43,320,200, -.